Liturgy and non-colonial thinking: Speaking to and about God beyond ideology, religion and identity politics – Towards non-religion and a unbearable freedom in Christ - Meylahn, Johann-Albrecht (HTS teologiese studies, 2021)
It has been argued that most countries that had been exposed to European colonialism have inherited a Western Christianity thanks to the mission societies from Europe and North America. In such colonial and post-colonial (countries where the political administration is no longer in European hands, but the effects of colonialism are still in place) contexts, together with Western contexts facing the ever-growing impact of migrants coming from the previous colonies, there is a need to reflect on the possibility of what a non-colonial liturgy, rather than a decolonial or postcolonial liturgy, would look like. For many, postcolonial or decolonial liturgies are those that specifically create spaces for the voice of a particular identified other. The other is identified and categorised as a particular voice from the margins, or a specific voice from the borders, or the voices of particular identified previously silenced voices from, for example, the indigenous backyards. A question that this context raises is as follows: Is consciously creating such social justice spaces – that is determined spaces by identifying particular voices that someone or a specific group decides to need to be heard and even making these particular voiceless (previously voiceless) voices central to any worship experience – really that different to the colonial liturgies of the past? To give voice to another voice, is maybe only a change of voice, which certainly has tremendous historical value, but is it truly a transformation? Such a determined ethical space is certainly a step towards greater multiculturalism and can therefore be interpreted as a celebration of greater diversity and inclusivity in the dominant ontology. Yet, this ontology remains policed, either by the state-maintaining police or by the moral (social justice) police.Contribution: In this article, a non-colonial liturgy will be sought that goes beyond the binary of the dominant voice and the voice of the other, as the voice of the other too often becomes the voice of a particular identified and thus determined victim – in other words, beyond the binary of master and slave, perpetrator and victim, good and evil, and justice and injustice, as these binaries hardly ever bring about transformation, but only a change in the face of master and the face of the slave, yet remaining in the same policed ontology.